Relationship between gingival recession and tooth brushing habits (Bangladesh Journal of Medical Science, 2024)
Background: Gingival  recession  is  a  common  periodontal  condition  that  can  lead to aesthetic and functional problems. Tooth brushing habits have been suggested to be associated with gingival recession, but the evidence on this relationship is limited.Aim: To  investigate  the  relationship  between  gingival  recession  and  tooth brushing habits in a sample of 100 patients.Methodology: A  cross-sectional  study  was  conducted  on  100  patients  aged  between 20  and  60  years  who  presented  to  a  dental  clinic.  Demographic  data, tooth  brushing  habits,  and  gingival  recession  depth  were  recorded. Descriptive  statistics  were  used  to  summarize  the  data,  and  logistic regression  analysis  was  performed  to  investigate  the  association between tooth brushing habits and gingival recession.Results: The  mean  age  of  the  participants  was  40  years,  and  52%  of  the participants  were  female.  The  mean  gingival  recession  depth  was  1.8 mm  (SD=0.7).  Majority  of  the  participants  brushed  their  teeth  twice a  day  (65%),  used  manual  tooth  brushes  (72%),  used  circular  method for tooth brushing (54%), spent 2-3 minutes on tooth brushing (60%), and dental floss was the most commonly used additional oral hygiene aid  (60%).  The  bivariate  correlation  analysis  showed  a  statistically significant  positive  correlation  between  gingival  recession  and frequency of tooth brushing (r=0.28, p=0.01).Conclusion: The  findings  of  this  study  suggest  that  tooth  brushing  habits  are significantly  associated  with  the  development  and  progression  of gingival  recession.  Thus,  oral  health  professionals  should  educate their  patients  about  the  proper  tooth  brushing  techniques  and  the  use of additional oral hygiene aids to prevent the development of gingival recession.Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 846-850